Clinical Observation on the Treatment of Chronic Subjective Dizziness by the Herbal-Scraping Duplex Method Based on Holographic Theory. (24th January 2022) - Luo, Huanwen; Liu, Caidan; Xiao, Ziwei; He, Yana
Abstract : Chronic subjective dizziness (CSD) is a chronic, subjective, nonrotational dizziness and instability caused by mental or physical factors, and patients generally have no existing vestibular system diseases. Clinically, antianxiety drugs are often used for symptomatic treatment with mediocre effects. This study observed the clinical efficacy of the herbal-scraping duplex method in the treatment of CSD based on the holographic theory. 180 patients with CSD were randomly and equally divided into group A ( n  = 60) who received fluoxetine hydrochloride, group B ( n  = 60) who received fluoxetine hydrochloride combined with holographic soup, and group C ( n  = 60) who received fluoxetine hydrochloride, holographic soup, and holographic scraping combined with five-element music. The effects of the 3 different treatment modalities on patients' vertigo symptoms, traditional Chinese medicine (TCM) symptoms, anxiety and depression status, sleep quality, and fatigue level were observed. The safety of medication and the recurrence after discontinuation were observed. The results showed that group C was better than group B and group A in terms of improvement in all of the above indicators, and group B was better than group A (P < 0.05 ). The total efficiency of Chinese and Western medicine was better in groups C and B than in group A (P < 0.05 ). No statistical difference was seen in the comparison of adverse reaction rates between the 3 groups (P > 0.05 ). After 1 month of drug discontinuation, the recurrence rates in groups C and B were lower than those in group A (P < 0.05 ). This suggests that the clinical efficacy and safety of applying the herbal-scraping duplex method based on holographic theory for the treatment of CSD is ideal and has the value of promotion.